ESTRATEGIAS AUDIOVISUALES PARA EL DESARROLLO DEL NIVEL DE ATENCIÓN, DE LOS NIÑOS DE TERCER AÑO DE EDUCACIÓN GENERAL BÁSICA, DE LA UNIDAD EDUCATIVA MILTON REYES, DE LA PARROQUIA MALDONADO, CANTÓN RIOBAMBA PROVINCIA DE CHIMBORAZO, PERIODO 2013-2014 - Cárdenas Soria, Miriam Katherine (2016)
The present research work Audiovisual Strategies for the development of level of care, was deployed with children in third year of Basic Education, Educational Unit "Milton Reyes" in Riobamba during the school year 2014- 2015, the study is based on the constructivist theory of Jean Piaget and Ausubel to reach a meaningful and lasting learning in children. The focus of the scientific foundations began with aspects: philosophical, epistemological, pedagogical, psychological, sociological, and legal, while the theoretical aspect focuses on the independent variable corresponding to the Audiovisual Strategies and the dependent related to Development level of Attention in children. The research design is documentary and De Campo, Exploratory correlational type and using the methods: scientific, inductive, deductive and Analytical Synthetic; The technique used was a survey based on a structured questionnaire to students in the third year of general basic education, aiming at first to show the problem and then find out whether it has achieved decrease and direct observation based on a observation sheet, designed for teachers and school psychologist, with these data we proceeded to the development of statistical tables and charts, for the analysis and interpretation of results. With the implementation of the proposal "Learning Applying", centered on a series of practical and motivating activities, which are developed based on the use of visual strategies directly related to the levels set in the Update and Strengthening Basic General Education Curriculum 2010 for thirdyear.